Protein glycosylation of extracellular vesicles from ovarian carcinoma cells - Gomes, Joana Raquel Afonso (2018)
Extracellular vesicles (EVs) are released by almost all types of cells, including tumor, immune and stem cells, and are also present in body fluids like saliva, urine, breast milk and malignant ascites. EVs have a unique cargo of proteins, lipids and nucleic acids, and conserve characteristics from donor cells.